Price of Electricity vs Different Heating Technologies in Czech Republic - Mikolas, Milan; Bartonova, Jana; Magnuskova, Jana; Letavkova, Dagmar (Communications - Scientific letters of the University of Zilina, 2014)
This paper analyses both individual components of the price of electricity and the electricity rates as related to individual modes of heating. The price development has been monitored and assessed since July 1, 2001, i.e. the date on which the ‘Price Decree of the Energy Regulation Office, No. 5/2001’ entered into force concerning introduction of new rates and prices of electricity for households and businesses. Primarily, the rate, D 02d, was chosen for assessment. This rate is used by the majority of households as they use gas or solid fuels for heating. Further, the rate, D45 d, for direct electric heating, and rates, D55 d and D 56 d, for heating by thermal pumps were also subject of assessment. Both the development trends and the comparison of the investigated rates of electricity make it obvious that prices of electricity will continue to be rising in the long-term perspective.